2021
DOI: 10.3390/su132011269
|View full text |Cite
|
Sign up to set email alerts
|

When Harmful Tax Expenditure Prevails over Environmental Tax: An Assessment on the 2014 Mexican Fiscal Reform

Abstract: This article examines the role of environmental taxation in mitigating environmental problems and contributing to sustainability in Mexico. It focuses on environmental tax revenues and tax expenditures since the 2014 Public Financial Reform (PFR), according to pro- or anti-environmental orientation. The research carried out combines the study of the regulation of the selected tax instruments, their classification and the empirical analysis of the tax revenues and tax expenditures associated with the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…The alternative hypothesis is that at least one element of the coefficient matrix Φ 𝑗 is significantly non-zero. 4 The statistics are as follows:…”
Section: Determination Of the Lag Order Of The Var Modelmentioning
confidence: 99%
“…The alternative hypothesis is that at least one element of the coefficient matrix Φ 𝑗 is significantly non-zero. 4 The statistics are as follows:…”
Section: Determination Of the Lag Order Of The Var Modelmentioning
confidence: 99%
“…López Pérez et al, (2021) found that since 2014, Mexico has levied environmental taxes in a small range and extremely low carbon emission prices, resulting in less income from environmental taxes. In order to improve the environment and increase environmental tax revenue, it should be necessary to significantly expand the scope of environmental tax collection and accelerate the increase of environmental tax rates [19]. Hu et al, (2020) collected data on more than 100,000 sewerage charges and sewerage charges from 4300 sewage companies in Yunnan Province, China in 2017.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Environmental taxes (green taxes) has potentially great effects on the environment also including energy taxes, transportation taxes, pollution taxes, and others [18]. Environmental taxes are an economic tool for environmental protection [22].…”
Section: Introductionmentioning
confidence: 99%